Air quality and water quality monitoring using XBee and internet of things - Gehlot, Anita; Singh, Rajesh; Samkaria, Rohit; Choudhary, Sushabhan; De, Aisik; ., Kamlesh (International Journal of Engineering and Technology, 2018)
There are numbers of disadvantage in the current existing systems for water quality monitoring which are generally limited to only a few varieties of parameter provide when there and need to be sending through manual operation. This type of security systems required a device which could send alert signal to the sub – stations and is very time consuming process. The quick warning or alert is not possible in the current existing system because they need some manual operation to be performed which could send the data and this cause a huge casualty because sometimes if the area is not in taken care of then it may cause huge causality to human as well as marine habitats. For such condi-tions a system required which automatically reads the sensor values (parameters) compares them with the threshold of fresh air and water parameters and if this level is above the threshold then automatically send alert with the pin point location to the sub – stations.